2008
DOI: 10.1111/j.1463-1318.2008.01542.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical bowel preparation and antibiotic prophylaxis in colorectal surgery: use by and opinions of Spanish surgeons

Abstract: There is general agreement on AP. MBP remained a common practice among Spanish colorectal surgeons except for right colonic resection. Surgeons with more case load and specialization used it significantly less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 22 publications
3
8
0
1
Order By: Relevance
“…Our results partially support the findings of other studies, which have shown that surgeons with greater activity in colorectal surgery used less MBP [11], that MBP in right colonic resection is used significantly less frequently than in left colonic or rectal resections [11], and that there is a discrepancy both between the subjectively rated usefulness of MBP and the effective use of MBP [12] and between the current evidence and the preoperative bowel preparation practices among surgeons globally [11][12][13]15]. The reason for the latter is largely unknown and might be caused by aesthetic and practical factors, especially in laparoscopic surgery.…”
Section: Discussionsupporting
confidence: 95%
See 4 more Smart Citations
“…Our results partially support the findings of other studies, which have shown that surgeons with greater activity in colorectal surgery used less MBP [11], that MBP in right colonic resection is used significantly less frequently than in left colonic or rectal resections [11], and that there is a discrepancy both between the subjectively rated usefulness of MBP and the effective use of MBP [12] and between the current evidence and the preoperative bowel preparation practices among surgeons globally [11][12][13]15]. The reason for the latter is largely unknown and might be caused by aesthetic and practical factors, especially in laparoscopic surgery.…”
Section: Discussionsupporting
confidence: 95%
“…The rate of use of antimicrobial prophylaxis in the current study (100%) compared favorably with previously published data [11,12]; in contrast, the parenteral route of administration of antibiotics in colorectal surgery in Switzerland was preferred (100%), whereas Spanish and US surgeons use orally administered antibiotics as well in 13.8% and 86% of patients, respectively, or in a combination of both. Parenteral administration yielded similar results compared with a combination of parenteral and oral prophylaxis [10].…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations